Att gestalta tillsammans med förebilder - Tenje Persson, Cecilia (2021)
The Eastern cemetery in Malmö, designed by the architect Sigurd Lewerentz just over 100 years ago, is a valuable architectural heritage. The following master thesis explores the challenging task of how to develop and care for such an architectural heritage, a task which requires knowledge not only of the specific location, but also the architect as well as cemetery architecture and design. With a starting point in the architectural competition for the Eastern cemetery memorial grove, announced by Movium, SKKF and Stenindustriförbundet, a design project of a specific area of the cemetery has explored connections of how studies of role models can support or affect the suggested designs. The design process studies characteristics of the Architect Sigurd Lewerentz such as landscape modelling, large scale design, his distinct design elements, thorough material knowledge as well the importance of the horizontal line. Additionally, other role models within the field of cemetery design is explored to broaden the view of how cemeteries may be designed, both in its entirety as well more specifically memorial groves. Finally, there is a comparison of similarities and differences between the design proposal and the studied role models.The design makes use of the largescale attributes which Lewerentz worked with, his specific design elements and the horizontal line. It is concluded that the studies of role models support the process with inspiration and has a significant impact of the result.